Relationship between infertility and psychiatric disorders - Sandra Ostrowska; Małgorzata Stróżna; Ivan Alekso; Piotr Arkadiusz Chil; Marta Pyziołek; Wiktoria Brzezińska; Klaudia Kowalczyk (Journal of Education, Health and Sport)
Introduction: Infertility is a serious health issue which affects milions of couples on the world. The dynamics of partnerships and social functioning, the effect of infertility on people's mental health, with a focus on family and gender disparities, are some of the most thorough literature evaluations.